A (re) configuração do espaço urbano de Santa Maria-RS sob a ótica territorial e das políticas habitacionais - Zanatta, Ricardo Nogueira (2011)
The dynamics of the modern world confer significant roles in cities, for these are the residence of the majority of the population. This has drawn the attention of experts and governments for the intense and rapid changes that these dynamics are generated in cities. Especially in the second half of the twentieth century, the government has sought a redefinition of its urban policies and urban planning, to meet and to minimize the effects of the intense demand for space in cities. Given the objective of this research, which is to review the housing policies in Santa Maria, especially in relation to the population inhabiting the areas at risk from the illegal occupation, it takes into account the issue of identity and territorial belonging of these populations . Walking through the intricacies of that investigation was necessary to place the real extent of housing projects and their effective implementation, as well as social and territorial consequences that such policies exercised by the study population. That said, there were no effective local actions until the federal government announced the housing policies for low-income populations, in order to intervene in that housing structure. Among the alternatives, the implementation of housing projects intended for low-income population of the city, listings in housing projects in the Department of Housing in the city, was the big step towards solving the housing problem. In this work, will be considered only two such projects in order to determine the true efficacy of the issue of urban planning. This fact shows that only a portion of the population is directly affected by lack of access to housing, this being the capital have not guaranteeing them access to a decent home. It was observed that there is a housing shortage in town, and yes, a poor distribution of where the lots are installed and their populations. Reality that exposes the problematic issue of housing as a recurring challenge to the government.